2019
DOI: 10.1002/ajmg.a.61324
|View full text |Cite
|
Sign up to set email alerts
|

Adverse effects of antipsychotic medication in patients with 22q11.2 deletion syndrome: A systematic review

Abstract: The 22q11.2 deletion syndrome (22q11.2DS) is a multisystem condition and the most prevalent microdeletion syndrome in humans. Approximately 25% of individuals with 22q11.2DS receive antipsychotic treatment. To assess whether patients with 22q11.2DS are vulnerable to adverse effects of antipsychotic medication, we carried out a literature review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…Furthermore, clozapine or quetiapine in combination with the valproic acid was suggested to be effective in the management of psychosis. A recent systemic review, which examined the adverse effects of antipsychotic medications in patients with VCFS, concluded that a causal relation between antipsychotic medication and the reported adverse effects could not be established in the majority of cases as the syndrome itself can present with antipsychotic‐related side effects such as seizures and cardiac pathology 3 . Lithium is known to be effective and well tolerated in pediatric patients for treatment of bipolar 1 disorder 4 …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, clozapine or quetiapine in combination with the valproic acid was suggested to be effective in the management of psychosis. A recent systemic review, which examined the adverse effects of antipsychotic medications in patients with VCFS, concluded that a causal relation between antipsychotic medication and the reported adverse effects could not be established in the majority of cases as the syndrome itself can present with antipsychotic‐related side effects such as seizures and cardiac pathology 3 . Lithium is known to be effective and well tolerated in pediatric patients for treatment of bipolar 1 disorder 4 …”
Section: Discussionmentioning
confidence: 99%
“…While there has been some suggestion to avoid certain psychotropic medications for individuals with 22q11.2 deletions (due to increased risk for seizures), 59 other studies have suggested that further evidence is needed before making psychotropic medication recommendations solely based on the presence of the CNV. 60,61 Currently, medication decisions should be made by a psychiatrist based on the current symptoms. Over-attribution of genetics (i.e., Feeling that the CNV determined their psychiatric illness and that it is "genetically ingrained"…”
Section: Discussing the Role Of The Cnv In The Etiology Of Psychiatri...mentioning
confidence: 99%
“…Exploring the role of psychotropic medication(s) and encouraging appropriate consultation with a psychiatrist may also be helpful. While there has been some suggestion to avoid certain psychotropic medications for individuals with 22q11.2 deletions (due to increased risk for seizures), 59 other studies have suggested that further evidence is needed before making psychotropic medication recommendations solely based on the presence of the CNV 60,61 . Currently, medication decisions should be made by a psychiatrist based on the current symptoms.…”
Section: Scenario 2: Identifying a Psychiatric Susceptibility Cnv In ...mentioning
confidence: 99%
“…Similar to our recommendations for children, management and treatment should be planned in the context of any cognitive or physical comorbidities, and pharmacotherapy should be based on a consideration of any medical comorbidities and sensitivity to adverse effects [ 44 •• ]. For 22q11.2DS a literature is building on psychopharmacotherapy effectiveness and side effects [ 44 •• ], particularly so for the administration of antipsychotics [ 52 , 53 , 54 ], but further research is needed for other CNVs.…”
Section: Clinical Evaluationmentioning
confidence: 99%